Carbon Nanotube Core Graphitic Shell Hybrid Fibers - Hahm, Myung Gwan; Lee, Jae-Hwang; Hart, Amelia H. C.; Song, Sung Moo; Nam, Jaewook; Jung, Hyun Young; Hashim, Daniel Paul; Li, Bo; Narayanan, Tharangattu N.; Park, Chi-Dong; Zhao, Yao; Vajtai, Robert; et al. (AMER CHEMICAL SOC, 2013)
A carbon nanotube yarn core graphitic shell hybrid fiber was fabricated via facile heat treatment of epoxy-based negative photoresist (SU-8) on carbon nanotube yarn. The effective encapsulation of carbon nanotube yarn in carbon fiber and a glassy carbon outer shell determines their physical properties. The higher electrical conductivity (than carbon fiber) of the carbon nanotube yam overcomes the drawbacks of carbon fiber/glassy carbon, and the better properties (than carbon nanotubes) of the carbon fiber/glassy carbon make up for the lower thermal and mechanical properties of the carbon nanotube yam via synergistic hybridization without any chemical doping and additional processes.
Keywords: THERMAL-CONDUCTIVITY; RAMAN; SCALE; YARNS; NEAT